Step-by-step needlecraft encyclopedia - Brittain, Judy (Dorling Kindersley, 1995)
This guide to needlecraft covers the techniques of knitting, crochet, knotting, macrame, netting, tatting, plaiting, rugmaking, weaving, embroidery, needlepoint, patchwork, quilting, applique and sewing.;Step-by-step drawings clarify the technical instructions, allowing the beginner to progress from simple designs to sophisticated creations. 2000 colour illustrations show the materials, tools and techniques required. Each sample is photographed